Structural descriptions framework of onboard repeaters schemas; Control and Communications (SIBCON) - Savenko I. I. Igor Igorevich; Sukhodoev M. S. Mikhail Sergeevich; Tsapko S. G. Sergey Gennadyevich; Simonov P. K. (2015, 2015)
Title screen